Malignant pleural mesothelioma in a kidney transplant recipient - Wasinee Traipipitsiriwat (2022)
Post-transplantation malignancy is one of the most common complication-related mortality in transplant recipients. Here, we report the case of a kidney transplant patient for 2 years with malignant pleural effusion that was subsequently diagnosed as malignant pleural mesothelioma.